THE EXPERIMENTAL PROGRAM "DEVELOPING SOCIAL INTELLIGENCE IN PRIMARY SCHOOL STUDENTS" - GUȚUL Aliona (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article presents an Experimental Program designed to enhance the social intelligence of primary school students. This period is crucial in developing intellectual, artistic, moral, and social feelings in children. The program is designed for children who exhibit limited knowledge in understanding the logical progression of complex interaction situations and the significance of individual behaviour in these scenarios. Consequently, they face difficulties in comprehending and anticipating human behaviour, which, in turn, hinders the effective establishment of interpersonal relationships, the achievement of desired goals, and favourable social adaptation. Teaching methods and activities included in the program have been tailored to the specific age group and the domains of social and emotional development. This program is founded on robust research and pedagogical practices aimed at supporting the development of social intelligence in primary school children. The results of this experimental research offer a crucial understanding of the effectiveness of educational approaches targeting the enhancement of social intelligence in young children. This study provides a practical perspective on how education can contribute to the development of essential social and emotional skills among primary school students.